2022
DOI: 10.1590/s1677-5538.ibju.2022.0194
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter comparative study of open, laparoscopic, and robotic pyeloplasty in the pediatric population for the treatment of ureteropelvic junction obstruction (UPJO)

Abstract: Introduction: Dismembered open pyeloplasty described by Anderson and Hynes is the "gold standard" for the treatment of ureteropelvic junction obstruction. The aim of our study was to compare the results of open (OP) vs laparoscopic (LP) vs robotic (RALP) pyeloplasty. Material and Methods: A multicenter prospective review was conducted of pyeloplasty surgeries performed at five high-volume centers between 2014 and 2018. Demographic data, history of prenatal hydronephrosis, access type, MAG3 renogram and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Finally, providing a benefit from the cosmetic endpoint can also lead to it becoming the preferable approach. By using a multi-institutional approach, with a large number of patients, the present study highlighted the main reasons why the minimally invasive is becoming the preferable option to perform a pyeloplasty (1). This study showed that the MIS approach both laparoscopically and robotically achieved similar success and complication rates but provided a benefit in the recovery with a shorter hospital length of stay.…”
Section: Commentmentioning
confidence: 61%
“…Finally, providing a benefit from the cosmetic endpoint can also lead to it becoming the preferable approach. By using a multi-institutional approach, with a large number of patients, the present study highlighted the main reasons why the minimally invasive is becoming the preferable option to perform a pyeloplasty (1). This study showed that the MIS approach both laparoscopically and robotically achieved similar success and complication rates but provided a benefit in the recovery with a shorter hospital length of stay.…”
Section: Commentmentioning
confidence: 61%
“…Fourth, robotic surgery has better ergonomics that helps alleviate the fatigue of surgeons during surgery. Fifth, performing the refined operation in a limited space reduces secondary injuries ( 6 , 14 17 ). Finally, the learning curve of robot surgery is short, and is significantly shorter in surgeons with considerable LP experience.…”
Section: Discussionmentioning
confidence: 99%
“… 16 The success rate and recurrence rate of LP are similar to those of open pyeloplasty. 17 The advantages of LP include reduced pain, a shorter hospital stay, and a better cosmetic effect on the abdominal wall. 16 The treatment decision for UPJO was historically based on clinical symptoms and auxiliary examination results.…”
Section: Discussionmentioning
confidence: 99%